An Analysis of Vegetation Cover Degradation as an Indicator of Desertification in Al-Jabal Al-Akhdar Region (Abhat Journal, 2025)
This study aimed to analyze the climate classification of the Jabal Akhdar region in Libya and monitor vegetation density deterioration as a desertification indicator across three models: Köppen, Emberger, and Thornthwaite. Remote sensing data from Landsat 5 and Sentinel-2B (2000-2024) were processed using GIS tools. The findings indicated that Emberger’s classification best represented the region, dividing it into four climatic zones. Dense vegetation declined by 78.58%, while very sparse vegetation expanded by 46.56%. In the humid zone (Köppen), dense vegetation decreased by 79.59%, whereas the very sparse vegetation surged by 803.7%. In the semi-humid zone, dense vegetation diminished by approximately 81% (Emberger and Thornthwaite). Desert and arid zones showed the most significant shift toward very sparse vegetation in all three models. The study recommended enhancing environmental monitoring via remote sensing, promoting sustainable agriculture, implementing reforestation programs, and enforcing policies for the conservation of natural resources
Keywords: Jabal Akhdar Region; Climate Classification; Geographic Information Systems (GIS); Desertifi-cation Indicators; Vegetation Cover Degradation